Ocular trauma score as a visual prognostic factor of open globe injuries in a hospital of southern Brazil - Deud,Beatriz Gubert (2021)
ABSTRACT Purpose: To compare the visual acuities predicted by the Ocular Trauma Score and each one of the Ocular Trauma Score variables with the final visual acuities of the victims of open globe injuries in a southern Brazil hospital. Methods: A total of 120 eyes of 119 individuals with open globe injuries were analyzed in this cross-sectional retrospective study that was developed in a university hospital. The information on age, sex, affected eye, trauma mechanism, and other data (such as initial visual acuity, the presence of globe rupture, perforating injury, endophthalmitis, retinal detachment, and afferent pupillary defect) were used to calculate the Ocular Trauma score, and the final visual acuities of all patients were retrieved from the patients’ medical records. Results: We noted an agreement between the visual acuity predicted by the Ocular Trauma Score and the final visual acuity in our study. An isolated analysis of the variables demonstrated significance with regard to the initial visual acuity (p<0.001), retinal detachment (p=0.001), and afferent pupillary defect (p=0.004). No significant differences were detected between the final visual acuities and those determined by the Ocular Trauma Score system for the present study population. Conclusions: The Ocular Trauma Score can be applied for the determination of the visual prognoses of victims of open globe injuries. The most significant variables in this predictive analysis are initial visual acuity, retinal detachment, and afferent pupillary defect. Prospective studies with larger sample sizes are required to confirm our findings.